Smooth particle hydrodynamics simulation of damage induced by a spherical indenter scratching a viscoplastic material. (1st March 2016) - Leroch, S.; Varga, M.; Eder, S.J.; Vernes, A.; Rodriguez Ripoll, M.; Ganzenmüller, G.
Abstract: We present an implementation of a (mesh-free) smooth particle hydrodynamics (SPH) algorithm, intended for the application to solid bodies, and use it to simulate scratch-induced surface damage on an elasto-viscoplastic material. If conventional SPH is used to simulate solids, an unphysically high artificial viscosity is required to damp strong oscillatory modes and thus stabilize the system. To overcome these intrinsic difficulties associated with modeling solid bodies, the recently implemented so-called total-Lagrangian SPH utilizes an hourglass control scheme similar to what is known from finite element algorithms. Elasto-viscoplastic material properties are modeled by using the Mie–Grüneisen equation of state and the Johnson–Cook model. The material parameters are selected to reproduce the strain-stress behavior of annealed oxygen-free high conductivity copper. The spherical indenter is modeled as a rigid sphere. The topographies of the calculated scratch-induced surface damage are in excellent agreement with experimental scratch tests carried out at comparable normal loads. We also calculate the real contact area between the indenter and the surface, allowing a sound estimation of the scratch hardness.